Endometriosis of the Terminal Ileum: A Diagnostic Dilemma - Kerem Karaman; Emel Ebru Pala; Umit Bayol; Ozlem Akman; Mustafa Olmez; Saime Unluoglu; Safak Ozturk (Hindawi Limited, 2012)
Endometriosis is characterized by the presence of endometrial tissue consisting of glands and/or stroma located outside the uterus. Involvement of the terminal ileum is extremely rare. Preoperative distinction of ileal endometriosis from other diseases of the ileocecal region is difficult in terms of clinical presentation, symptomatology, radiological appearance, and surgical and pathological findings. We report a case initially diagnosed as Crohn's disease due to a longstanding diarrhea with subsequent intestinal obstruction, but finally diagnosed as ileal endometriosis by histopathological evaluation after resection of the involved segment.